Factors Affecting Nurse Caring Behavior - Yoani M. Vianney Bita Aty; Elisabeth Herwanti; Aemilianus Mau; M. Ibraar Ayatullah; Fialisa Asriwhardani (JURNAL INFO KESEHATAN, 2020)
Caring behavior is the center of nursing practice, a very dynamic technique, where nurses work with care for their patients. The better the nurse's caring behavior in providing nursing services to patients, the better the level of patient satisfaction with nursing services. Currently, there are nurses and other health workers who are not friendly enough in providing services. The objective of this study is to determine the factors that influence the caring behavior of nurses who work at the Regional Public Hospital of East Nusa Tenggara Province, which are age, gender, education, training, employment status, marital status, work stress, work motivation and respect for nurse caring behavior. This research is a type of quantitative research with a cross-sectional design. The population is all nurse administrators who work in 5 Regional Public Hospital of East Nusa Tenggara Province, amounting to 803 people. The number of samples of 161 nurses was taken by simple random sampling. Determination of the number of samples using the rule of thumb formula, namely 5 independent variables x 32 = 160 respondents. The instrument used was a questionnaire. Bivariate data analysis at a significant level of 5% (α = 0.05) using the Pearson Chi-Square test. Multivariate analysis using logistic regression test. The results showed that the factors that influence nurse caring behavior are employment status (p value 0.001) and motivation (p value 0.005). The results of the Odds Ratio (Exp. B) show that employment status is a determinant factor in the caring behavior of nurses in East Nusa Tenggara with an OR of 3,634, which means that nurses with civil servant status are 3.6 times more likely to behave in caring than nurses with contract employment status. It is suggested to examine other factors that can influence the caring behavior of nurses who work at the Regional Public Hospital of East Nusa Tenggara Province.